An improved method for isolation of epithelial and stromal cells from the human endometrium - MASUDA, Ayako (J Reprod Dev, 2016)
We aimed to improve the efficiency of isolating endometrial epithelial and stromal cells (EMECs and EMSCs) from the human endometrium. We revealed by immunohistochemical staining that the large tissue fragments remaining after collagenase treatment, which are usually discarded after the first filtration in the conventional protocol, consisted of glandular epithelial and stromal cells. Therefore, we established protease treatment and cell suspension conditions to dissociate single cells from the tissue fragments and isolated epithelial (EPCAM-positive) and stromal (CD13-positive) cells by fluorescence-activated cell sorting. Four independent experiments showed that, on average, 1.2 × 10(6) of EMECs and 2.8 × 10(6) EMSCs were isolated from one hysterectomy specimen. We confirmed that the isolated cells presented transcriptomic features highly similar to those of epithelial and stromal cells obtained by the conventional method. Our improved protocol facilitates future studies to better understand the molecular mechanisms underlying the dynamic changes of the endometrium during the menstrual cycle.